2014
DOI: 10.3400/avd.cr.13-00108
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Axillary Graft Stump Syndrome: Report of Two Cases

Abstract: Late upper extremity embolic complications of occluded axillofemoral bypass graft (AxFG) or occluded axillo- axillary bypass graft (AxAG) are not frequently noted. A patient presented with acute right upper extremity thromboembolism 2 years after an AxFG occlusion. Computed tomography (CT) findings revealed kinking and occlusion of the axillary artery at the anastomosis. Another patient presented with acute left upper extremity thromboembolism 2 years and 6 years after an AxAG occlusion. CT indicated a thrombu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“… 4 , 5 , 6 , 7 , 9 , 10 In the few case reports describing the syndrome, management techniques of the axillary stump include both endovascular and open surgical options in combination with anticoagulation 4 , 5 , 6 , 7 , 8 , 9 , 10 ( Table ). Kanamitsu et al 10 suggested that treating an axillary stump is not always necessary, but once a thromboembolic event occurs, they recommend resection of the graft with arterial reconstruction. In their case, when initially treated with anticoagulation, as in the patient presented here, recurrent thromboembolism was reported.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“… 4 , 5 , 6 , 7 , 9 , 10 In the few case reports describing the syndrome, management techniques of the axillary stump include both endovascular and open surgical options in combination with anticoagulation 4 , 5 , 6 , 7 , 8 , 9 , 10 ( Table ). Kanamitsu et al 10 suggested that treating an axillary stump is not always necessary, but once a thromboembolic event occurs, they recommend resection of the graft with arterial reconstruction. In their case, when initially treated with anticoagulation, as in the patient presented here, recurrent thromboembolism was reported.…”
Section: Discussionmentioning
confidence: 87%
“… 4 , 5 , 6 , 7 , 8 , 9 , 10 A blind stump and Y configuration of the bypass have been postulated as mechanisms for thromboembolic events in AxFSS. 4 , 5 , 6 , 7 , 9 , 10 In the few case reports describing the syndrome, management techniques of the axillary stump include both endovascular and open surgical options in combination with anticoagulation 4 , 5 , 6 , 7 , 8 , 9 , 10 ( Table ). Kanamitsu et al 10 suggested that treating an axillary stump is not always necessary, but once a thromboembolic event occurs, they recommend resection of the graft with arterial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations